Analysis of Health Sector Gender Equality and Social Inclusion Strategy 2009 of Nepal - Mahara, GB; Dhital, SR (Kathmandu University Medical Journal, 2015)
The policy on gender equality and social inclusion (GESI) in health sector of Nepal is formulated in 2009 targeting toward poor, vulnerable, marginalized social and ethnic groups. Gender inequality and social discrimination are a social problem that affect on individual health finally. The main objective of this paper is to critically analysis and evaluates the Government’s strategy on health sector gender equality and social inclusion in Nepal. We collected published and unpublished information assessing the public health, policy analysis and research needs from different sources. A different policy approaches for the analysis and evaluation of GESI strategies is applied in this paper. Universal education, community participation, individual, group and mass communication approaches, and social capital are the key aspects of effective implementation of policy at target levels.Kathmandu University Medical Journal Vol.12(2) 2014: 157-160